P PENGEMBANGAN PADI GOGO PRODUKSI TINGGI HASIL INDUKSI MUTASI PADI LOKAL SULAWESI TENGGARA (DEVELOPMENT OF HIGH YIELD UPLAND RICE THROUGH MUTATION INDUCTION OF LOCAL RICE SOUTH SULAWESI) - ni wayan sri suliartini (CROP AGRO, Scientific Journal of Agronomy, 2020)
ABSTRACT Rice is the main staple food for Indonesian people. The demand for rice has increased every year which must be followed by an increase in production. This study aims to obtain rice mutant lines that have high production. The study was conducted at the Experiment Field of the Faculty of Agriculture, Halu Oleo University. The experimental design used was a randomized block design with three replications. The treatments consisted of six lines namely G1 = K3D3 203 34 (Mutant), G2 = K3D1 6 21 (Mutant), G3 = K3D0 (Parent), G4 = K3D1 104 36 (Mutant), G5 = K3D1 104 35 (Mutant), G6 = Watanta (Check 1) and G7 = Wangkariri (Check 2). The data were analyzed using ANOVA followed by Dunnet Test. Observations showed that all upland rice mutants had a higher number of productive tillers than check 2 (G6) but were equal to parent/check 1, panicle length higher than parent/check 1 (G3) but equal to check 2, weight 100 pithy grain and harvest dry grain weight are higher than parent/check 1 and check 2. All mutants have the potential to be developed into high-yielding upland rice lines. Keywords: upland rice, gamma irradiation, mutant, high yield.